Model Pemetaan Wisata Halal Sebagai Upaya Peningkatan Kunjungan di Banda Aceh - Ihsanuddin Ihsanuddin; Abdus Salam; Fauzan Putraga Al Bahri (Jurnal EMT KITA, 2019)
Halal tourism in Indonesia has good economic prospects as part of the national tourism industry. The tourism industry aims not only to provide material and psychological aspects for tourists themselves but also to contribute to increase government revenue. Halal Tourism Mapping System is basically a form of mapping using Google's advanced features and maps as an effort to collect data mapping of halal destination data in order to become a media and promotion for halal tourism search with the label "The Light Of Aceh". This effort is a form of the initial step as a regional promotion, especially halal attractions so that they are indexed by giant search engines such as Google, Yahoo, and Bing. Government and community expectations of visitors from both local and international came to be a problem in terms of technology because they do not understand it and understand the ease of mapping features of an area. It is hoped that the Halal Tourism mapping system with the label "The Light of Aceh" can realize the dream of the community and the government to increase visitors from outside the region and abroad. Predictions of the results obtained from the results of this study are to help tourists and visitors in obtaining information on halal attractions in Banda Aceh, as well as helping the Government and the public in encouraging increased foreign tourist arrivals.